The Use of Assistive Learning Technology in Learning Mathematics for Hearing Impairment Students - Fadhilah Rahmawati; Megita Dwi Pamungkas (Indonesian Journal of Mathematics Education, 2023)
The problem in this study is the limitations of mathematics learning media that are suitable for the conditions of deaf students. So, the researcher developed an assistive math teaching aid for deaf students. This study aimed to determine the effect of using assistive learning technology given to hearing impairment students. This research focuses on improving the representation ability of hearing impairment students on the topic of fractional operations. This research is a quantitative study with a pretest-posttest control design. This research was conducted on hearing impairment students with mild to severe categories without intellectual impairment. The number of hearing impairment students involved was 12 students at a special type B school in Magelang City, Indonesia. The N-Gain test was used in this study to measure the improvement in the representation ability of hearing impairment students. Based on the results of the study, it was concluded that assistive learning positively affected the representation ability of hearing impairment students. Based on the results of the N-Gain test, an increase of 0.972 was obtained. In addition, the use of assistive learning technology provides a learning experience that trains the independence of hearing impairment students. The teacher's role as a facilitator in the classroom can be maximized because topics can be accessed anywhere and anytime.